The lost hero - Riordan, Rick (New York : Disney/Hyperion Books, 2010)
Jason, Piper, and Leo, three students from a school for "bad kids," find themselves at Camp Half-Blood, where they learn that they are demigods and begin a quest to free Hera, who has been imprisoned by Mother Earth herself.
Sentence length: 2 (easy) Word frequency: 1 (very easy)
660L
AR
Accelerated Reader
Reading Counts!
Lexile
Keywords: Hera -- (Greek deity) -- Fiction; Gaia -- (Greek deity) -- Fiction; Mythology, Greek -- Juvenile fiction; Camps; Monsters; Action & Adventure; Mythology, Greek; Adventure stories, American; Fantasy fiction; Young adult fiction; Occult fiction; Young Reader's Choice Award: Junior division: Winner -- 2013.; Action and adventure fiction; Fantasy fiction; Fiction